An Analysis Of Students' Strategies To Overcome Anxiety In Speaking English Of Grade 8 Students At Mts Pancasila Kota Bengkulu - Ningrum, Amanda Novry Oktavia; Zasrianita, Fera; Febriani, Hanura (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the strategies used by eighth-grade students at MTs Pancasila Kota Bengkulu in overcoming English speaking anxiety. This study employed a qualitative descriptive method with data collected through questionnaires and interviews. The data were analyzed descriptively to identify the strategies most frequently used by students in dealing with speaking anxiety. The results revealed that five strategies were identified, namely Preparation, Relaxation, Positive Thinking, Peer Seeking, and Resignation. Among these strategies, Peer Seeking was the most frequently used strategy with an average score of 85%, while Resignation was the least frequently used strategy with an average score of 69%. The findings indicate that peer support helps students increase their self-confidence, feel more comfortable, and reduce fear when speaking English in the classroom. This study concludes that social support and a positive classroom environment play an important role in helping students reduce speaking anxiety and increase their willingness to speak English.